East–West similarities and differences in the surface and deep northern Arabian Sea records during the past 21 Kyr - Gupta, Anil K.; Mohan, K.; Sarkar, Sudipta; Clemens, Steven C.; Ravindra, Rasik; Uttam, Rajesh K. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
This study analyses monsoon proxy Globigerina bulloides from Ocean Drilling Program (ODP) Hole 723A (western Arabian Sea) and Hole ABP-25, 02 (northeastern Arabian Sea) as well as dominant benthic foraminifera, pteropods, total organic carbon (TOC), Inorganic Carbon (IC) and stable isotope values of benthic foraminifera from Hole ABP-25, 02 to understand summer monsoon-driven changes in the western and eastern Arabian Sea and their impacts on deep-sea ventilation during the past 21 Kyr. We have also combined published TOC data from ODP Hole 724B to understand if deep-sea conditions in the Arabian Sea were same throughout the region during the studied interval. The summer monsoon was generally weaker during cold intervals including the Last Glacial Maximum, the Younger Dryas and the Bond events of the Holocene. From 20 to 10 Kyr, the deep northeastern Arabian Sea was better oxygenated with less organic carbon supply except during 14–12.5 Kyr when TOC values increased, indicating a weaker summer monsoon and a weak oxygen minimum zone (OMZ). The TOC values and the abundance of the eutrophic benthic foraminiferal species Bulimina aculeata, Melonis barleeanum and Uvigerina peregrina increased during the late Holocene whereas well-oxygenated, low organic carbon benthic species Sphaeroidina bulloides as well as pteropods decreased, indicating an intense OMZ and an increased supply of refractory organic material to the Arabian Sea. It is important to note that although the surface response to monsoon variability was more or less similar in the western and northeastern Arabian Sea, the deep-sea conditions show a marked contrast in the two regions during the past 21 Kyr.
id: 2100